LncRNA NR_030777 Alleviates Paraquat-Induced Neurotoxicity by Regulating Zfp326 and Cpne5. (31st July 2020) - Yang, Hongyu; Lin, Qingxia; Chen, Nengzhou; Luo, Zhousong; Zheng, Chunyan; Li, Jing; Zheng, Fuli; Guo, Zhenkun; Cai, Ping; Wu, Siying; Wang, Yuan-Liang; Li, Huangyuan
Abstract: Paraquat (PQ) is herbicide widely used in agricultural production. It is identified as an environmental toxicant that could lead to neurodegeneration damage. Parkinson's disease (PD) is a central nervous system degenerative disease that occurs in the elderly. Main risk factors for PD include genetic and environmental variables, but its specific mechanism is still not well understood. Emerging evidence suggests that long noncoding RNAs (lncRNAs) play an important role in PD. LncRNA NR_030777 has a full length of 2208 bp and is highly conserved among species. RNA profiling showed a significant alteration in lncRNA NR_030777 expression upon PQ-induced neurotoxicity. However, little is known on the functional relevance of lncRNA NR_030777 in the development of PQ. In this study, we discovered a vital protective role of lncRNA NR_030777 in PQ-induced neurotoxicity. The expression of NR_030777 correlates with elevated level of reactive oxygen species induced by PQ. In addition, activated expression of NR_030777 alleviates neurotoxicity by regulating the expression of Zfp326 and Copine 5. We report that lncRNA NR_030777 has a vital protective role in neurotoxicity induced by environmental toxicants such as PQ. This study could serve as an exemplary case for lncRNAs to be considered as a potential target for the prevention and treatment of PQ-induced neurodegenerative disorders such as PD.